PENGARUH PEMASARAN DIGITAL TERHADAP OMZET USAHA PADA MASA PANDEMI COVID 19 (STUDI PADA UMK DI KOTA SALATIGA) - Fevriera, Sotya; Saraswati, Birgitta Dian; Adhitya, Dhian; Siwi, Virgiana Nugransih; Wahyudi, Yustinus (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2023)
This study aims to identify the effect of using digital marketing on MSME business turnover in Salatiga City before and during the Covid-19 pandemic. The research sample is 134 businesses representing all small and medium enterprises in Salatiga City. The research uses data on the use of digital marketing by business actors in Salatiga City. The analysis technique uses descriptive statistics, qualitative analysis and regression models. The results show that the use of digital marketing has proven to have an effect on the turnover of SMEs during the Covid-19 pandemic. SMEs who did not use digital marketing during the Covid-19 pandemic had a lower turnover than SMEs who used digital marketing during the Covid-19 pandemic.